Using of the Neural Network to predict the Stock Prices and the extent of their Disclosure in the Financial Statements - Kendory, Emad; Obaid Ahmed, Khalid; Saad Jari, Ahmed (Opción, 2019)
Investing in stocks is fraught with long risks that makes it tough to manage and predict the choices out there to the investor. A decision making to an in- vestment can open up losses that accumulate them cause bankruptcy. There- fore, the extent of disclosure of stocks in the financial statements; in accord with the International Standard; is so important to investors as well as the different approaches to predict the future prices of stock. Among the foremost vital of those is that the neural network. The neural network depend upon the historical prices of stocks to expect the future prices and rank its importance. The researchers conclude that Facebook Inc. comply with the International Accounting Standard (IAS 1) as well as neural network ranks the relative importance of each item that affect the stock price estimate.. For purposes of this topic, the research divided this study into four sections. The first section included the methodology of research and some of the previous studies, the second section is targeted on the theoretical framework of the research, and the third section shows the application of research, while the fourth section was devoted to the foremost vital conclusions and recommendations reached by the researchers.